'Ecological concerns weren't the main reason why I took the bus, that association only came afterwards': on shifts in meanings of everyday mobility. Issue 6 (2nd November 2021) - Meinherz, Franziska; Fritz, Livia
ABSTRACT: Reducing the modal share of car travel in commuting implies challenging meanings of everyday mobility that tie commuting to driving. Existing research has focussed on describing ways in which everyday mobility is meaningful. However, why shifts in meanings occur remains largely unexplored. This article asks how meanings become ascribed to everyday mobility and identifies dynamics that play a role in shifts in those meanings. We analysed interviews with short distance commuters in two Swiss cities. Combining the analytical foci of the mobilities turn and practice theories, we developed a typology of four registers through which meaning is ascribed to everyday mobility (functional, hedonic, representative, habitual) and identified three sets of dynamics that play into shifts between these registers: i) dynamics related to the spatio-temporal complexity of everyday life, ii) dynamics emerging from different and changing social representations of mobility, and iii) dynamics tied to subjective experiences of everyday mobility. Our findings indicate that shifts in meanings and performances of everyday mobility must be analysed together, and that differences in how commuters ascribe meaning to everyday mobilities can reveal structural dynamics inhibiting the spread of pleasurable low-carbon everyday mobilities.